Complications of three deep sedation methods for magnetic resonance imaging - Solina Tith; Kirk Lalwani; Rongwei Fu (Wolters Kluwer Medknow Publications, 2012)
Background : Propofol and pentobarbital are commonly used to sedate children undergoing magnetic resonance imaging (MRI). Aim/Objective: To compare the safety of three types of sedation: intravenous propofol (PROP), mixed pentobarbital/propofol (PENT), and mixed pentobarbital group requiring supplemental sedation (PENT SUPP) regimens in pediatric patients following deep sedation (DS) for noncardiac MRI. Materials and Methods: We conducted a case-control study matching 619 cases with complications with 619 controls using data from our institution's sedation database for children deeply sedated for noncardiac MRI. Cases were defined as patients with any complication and we characterized complications from cases, and used a conditional logistic regression model to assess the association between three DS methods and occurrence of complications after adjusting for confounding variables. Results: We found that complications occurred in association with 794 (10.1%) of the 7,839 DSs performed for MRI between 1998 and 2008. Of the 794 cases, 619 cases met inclusion criteria for the study. Among the 619 cases that met inclusion criteria, 24 (0.3% of 7,839 DSs total) were associated with major complications. Type of sedation was significantly associated with the occurrence of complications, and the PENT group was associated with decreased odds of complications when compared to the PROP regimen (OR 0.68; 95% CI 0.46, 0.98; P=0.040) and compared to the PENT SUPP group (OR 0.60; 95% CI 0.31, 0.89; P<0.0001). Conclusions: DS with a pentobarbital technique was associated with decreased odds for complications when compared to a propofol-based technique or a pentobarbital technique requiring supplemental sedation.